Polylactic Acid-Based Patterned Matrixes for Site-Specific Delivery of Neuropeptides On-Demand: Functional NGF Effects on Human Neuronal Cells - Sindeeva, Olga A.; Kopach, Olga; Kurochkin, Maxim A.; Sapelkin, Andrei; Gould, David J.; Rusakov, Dmitri A.; Sukhorukov, Gleb B. (Frontiers in Bioengineering and Biotechnology, 2020)
The patterned microchamber arrays based on biocompatible polymers are a versatile cargo delivery system for drug storage and site- and time specific drug release on demand. However, functional evidence of their action on nerve cells, in particular their potential for enabling patterned neuronal morphogenesis, remains unclear. Recently, we have established that the polylactic acid (PLA)-based microchamber arrays are biocompatible with human cells of neuronal phenotype and provide safe loading for hydrophilic substances of low molecular weight, with successive site-specific cargo release on-demand to trigger local cell responses. Here, we load the nerve growth factor (NGF) inside microchambers and grow N2A cells on the surface of patterned microchamber arrays. We find that the neurite outgrowth in local N2A cells can be preferentially directed towards opened microchambers (site-specific NGF release). These results suggest the PLA-microchambers can be an efficient drug delivery system for the site- and time-specific delivery of neuropeptides, potentially suitable for guidance of human nerve cells.